2018
DOI: 10.12968/bjcn.2018.23.9.426
|View full text |Cite
|
Sign up to set email alerts
|

Community diabetes nurse specialists: service evaluation to describe their professional role

Abstract: This paper presents a service evaluation on the role of Community Diabetes Nurse Specialists (CDNS), which was undertaken as a response to various changes. Quantitative and qualitative data were captured over 6 months. It was found that GPs refer patients to CDNSs four times more frequently than other health professionals. The clinical care of CDNSs mainly relates to diabetes education, insulin, assessment and self-management. Telehealth is used twice as frequently as face-to-face communications. The CDNSs do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Although pharmacotherapeutic education in this study was conducted by a physician, education conducted by clinical pharmacists or nurses also effectively improves medication adherence (30,31). Moreover, effective education could also be conducted over the telephone (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmacotherapeutic education in this study was conducted by a physician, education conducted by clinical pharmacists or nurses also effectively improves medication adherence (30,31). Moreover, effective education could also be conducted over the telephone (32).…”
Section: Discussionmentioning
confidence: 99%
“…Penderita diabetik sangat berisiko terhadap kejadian luka kaki, pada umumnya kronis dan sulit penyembuhannya (Akbar, Malini, & Afiyanti, 2018). Hal ini disebabkan penderita DM rentan terkena infeksi yang erat hubungannya dengan pengembangan kuman pada lingkungan dengan kadar glukosa tinggi (McDowell & Boyd, 2018). Pasien diabetes akan mengalami setidaknya satu luka kaki selama hidup mereka dan sering berujung pada amputasi jari kaki, kaki atau tungkai.…”
Section: Pendahuluanunclassified
“…Penelitian ini dilaksanakan secara praktik langsung di rumah klien, sehingga memberi manfaat kepada subjek berupa suasana nyaman bagi klien untuk kapan pun tanpa harus keluar rumah di masa pandemic. Edu home care secara efektif meningkatkan minat dan kemampuan merawat kaki, sehingga dapat di pilih sebagai salah satu metode edukasi oleh perawat (McDowell & Boyd, 2018). Tingkat perawatan kaki berdasarkan usia menunjukkan bahwa sebagian besar responden yang melakukan perawatan kaki yang baik berusia rata-rata dibawah usia 55 tahun.…”
Section: Pembahasanunclassified
“…Several studies have shown the nurse’s success in identifying people with poorly controlled diabetes and helping them control the disease and reduce hospitalizations. 5 , 6 Other studies have shown the benefits of the nurse as a case manager for treating diabetes and their effect on HA1C and blood pressure control, especially for high-risk patients with poor control. 7 - 9 Another study investigated structured intervention by the clinic nurse for people with diabetes under routine follow-up of the family physician, compared to patients with family physician follow-up only.…”
Section: Introductionmentioning
confidence: 99%